Stromal architecture and periductal decorin are potential prognostic markers for ipsilateral locoregional recurrence in ductal carcinoma in situ of the breast. Issue 4 (26th July 2013) - Van Bockstal, Mieke; Lambein, Kathleen; Gevaert, Olivier; De Wever, Olivier; Praet, Marleen; Cocquyt, Veronique; Van den Broecke, Rudy; Braems, Geert; Denys, Hannelore; Libbrecht, Louis
Abstract : Aims: The incidence of ductal carcinoma in situ (DCIS) has increased since the introduction of screening mammography. Recurrence prediction is still not accurate, and could be improved by identifying additional prognostic markers. Periductal stroma actively participates in early breast cancer progression. Therefore, the aim of this study was to explore the prognostic potential of stromal characteristics in DCIS. Methods and results: Histopathological features and hormone receptor/HER2 status were analysed in a first cohort of 65 cases of DCIS with a median follow‐up of 112 months. Cox regression analysis revealed that myxoid stromal architecture was significantly associated with increased ipsilateral locoregional recurrence ( P = 0.015). Next, we performed immunohistochemical screening of nine stromal proteins in a second cohort of 82 DCIS cases, and correlated their expression with stromal architecture. Because reduced stromal decorin expression correlated most strongly with myxoid stroma ( P < 0.001), it was selected for further analysis in the first cohort. Patients with reduced periductal decorin expression had a higher risk of recurrence ( P = 0.008). Furthermore, HER2 overexpression was significantly associated with invasive but not with in situ recurrence ( P = 0.007). Conclusions: Periductal myxoid stroma and reduced periductal decorin expression seem to be prognostic for overall ipsilateral locoregional recurrence in DCIS, whereas HER2 expression might be a more specific biomarker for invasive recurrence.